Застосування реактивних вебфреймворків із використанням підходу "один раз, запускай скрізь" (write once, run everywhere) - Скворцов, В. Х. (ХНУРЕ, 2024)
This paper explores the "Write Once, Run Everywhere" principle in the context of using reactive web frameworks. The main objective is to examine the key aspects of cross-platform development, including the advantages, disadvantages, and core principles of this approach. The study analyzes the role of popular reactive frameworks such as React, Vue, and Angular in creating universal applications capable of running on various devices and operating systems. It discusses the challenges developers face when applying this principle and proposes strategies for overcoming them.
Keywords: реактивний вебфреймворк